Technology Transfer and Early Industrial Development: Evidence from the Sino-Soviet Alliance - Michela Giorcelli; Bo Li (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies the causal effect of technology and knowledge transfers on early industrial development. Between 1950 and 1957, the Soviet Union supported the "156 Projects" in China for building technologically advanced industrial facilities. We exploit idiosyncratic delays in project completion and the unexpected end of the Sino-Soviet Alliance, and show that receiving both Soviet technology and know-how had large, persistent effects on plant performance, while the effects of receiving only Soviet capital goods were short-lived. The intervention generated horizontal and vertical spillovers, and production reallocation from state-owned to privately owned companies since the late 1990s.
Keywords: L20; M20; N34; N64; O32; O33; 330; industrialization; technology transfer; knowledge diffusion; China